Drought and Water Scarcity Management Policy in England and Wales—Current Failings and the Potential of Civic Innovation - Grecksch, Kevin; Landström, Catharina (Frontiers in Environmental Science, 2021)
Drought management in England and Wales takes place in a narrow, confined governance space. Assessed against international literature on drought management, England and Wales show little innovativeness and little actual willingness to change. We ask how drought and water scarcity management is currently done, who is involved (or not) and, foremost, what are the current problems and deficiencies English and Welsh drought and water scarcity management that require attention. We are also interested in the question of what can be done to improve drought and water scarcity management in England and Wales. This research therefore explores how we can create a continuous relationship between the different actors contributing different levels of knowledge and we plead to widen the drought governance space in order to face the current and future water governance challenges. First, we present an empirically based critique of current drought and water scarcity management in England and Wales, highlighting the contrast between internationally available drought and water scarcity management options and what is currently applied in England and Wales. Second, we present and introduce Environmental Competency Groups, a methodology aiming to bring local residents’ experience-based knowledge of water management in relation to particular catchments to bear on the generation of scientific knowledge. It has been successfully trialed in relation to both droughts and flooding in England and Wales. We argue that this is a successful way to bring together people with different perspectives and knowledge in order to overcome the deficiencies of current drought and water scarcity management in England and Wales.